Partidos de gobierno en la era posneoliberal: paradigmas antagónicos y límites para una agenda de izquierda en América del Sur. Los casos del Frente Amplio, Alianza País y el Frente para la Victoria - Gallo, Adriana (2012)
Since the beginning of the XXIst century there has been an expansion of leftist movements and parties in Latin America, which have emerged as a viable and refreshing alternative to the neoliberal paradigm of the 90s. Our research will focus on three specific cases of party organization of each model: FA of Uruguay, characterised as institutionalist; Alianza País of Ecuador, deemed rupturist; and PJ/FPV of Argentina, generally identified as an ambivalent case. We tried to highlight, instead of the differences among them, the divergence between the implementation of an alternative model to the neoliberal paradigm, and a transformation that includes the leftist traditional banners.